Emotional state and poor school performance in children of Colombia - Bravo García, Leslie (2015)
In this paper the results of a study conducted on a sample of 201 children with poor academic performance, aged 5 to 12 years who conducted the Screening Test of Emotional Problems and Child Behavior (SPECI) are presented. The aim of this study was to determine the relationship between emotional problems and academic under achievement in children 5-12 years of an educational institution Sincelejo- Colombia.